Dukungan Komitmen Organisasi dan Kesejahteraan Psikologis terhadap Kinerja melalui Kepuasan Kerja: Perspektif Teori Pertukaran Sosial dan Teori Tuntutan-Sumber Daya Pekerjaan - Liana, Yuyuk; Zuhroh, Imama; Irawati, Rina; Erawati, Sherli Hesti (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effects of organizational commitment and psychological well-being on lecturer performance, with job satisfaction as a mediating variable, at private universities in Malang. Using a quantitative survey method, data from 82 lecturers selected via purposive sampling were analyzed with PLS-SEM. Results show that both organizational commitment and psychological well-being significantly influence performance, directly and indirectly through job satisfaction. These findings highlight the role of internal factors in supporting the tridharma of higher education. The study underscores the need for HR policies that enhance commitment, well-being, and satisfaction to drive sustained academic performance.